Estudio de factibilidad presupuestal para el desarrollo de un proyecto al costo de vivienda tipo interés social en la localidad de Teusaquillo. (2021)
The development of this research work aims to conclude under a judicious theoretical framework the budgetary feasibility for the development of a project at the cost of low-income housing in the town of Teusaquillo, Bogotá D.C. This perspective allows to know the minimum budgetary panorama for the acquisition of new housing in the locality; this, by optimizing the variables of studies and designs, cost of materials, cost of labor, procedures and licenses.